Prospects for Radiopharmaceuticals as Effective and Safe Therapeutics in Oncology and Challenges of Tumor Resistance to Radiotherapy - Ekaterina Nikolova; Dimitar Tonev; Nikolai Zhelev; Vladimir Neychev (SAGE Publishing, 2021)
The rapid advances in nuclear medicine have resulted in significant advantages for the field of oncology. The focus is on the application of radiopharmaceuticals as therapeuticals. In addition, the latest developments in cell biology (the understanding of the cell structure, function, metabolism, genetics, signaling, transformation) have given a strong scientific boost to radiation oncology. In this regard, the article discusses what is soon going to be a new jump in radiation oncology based on the already accumulated considerable knowledge at the cellular level about the mechanisms of cell transformation and tumor progression, cell response to radiation, cell resistance to apoptosis and radiation and cell radio-sensitivity. The mechanisms of resistance of tumor cells to radiation and the genetically determined individual sensitivity to radiation in patients (which creates the risk of radiation-induced acute and late side effects) are the 2 major challenges to overcome in modern nuclear medicine. The paper focuses on these problems and makes a detailed summary of the significance of the differences in the ionizing properties of radiopharmaceuticals and the principle of their application in radiation oncology that will shed additional light on how to make the anti-cancer radiotherapies more efficient and safe, giving some ideas for optimizations.